2017
DOI: 10.5005/jp-journals-10024-2006
|View full text |Cite
|
Sign up to set email alerts
|

Self-tapping Intermaxillary Fixation Screw: An Alternative to Arch Bar

Abstract: Introduction The use of intermaxillary fixation (IMF) in the treatment of faciomaxillary fractures is the key factor for reduction and immobilization. Various techniques of IMF have been described in the past and recently IMF screws have been introduced. This technique has various advantages, including ease of use, less time consumption, less trauma to the surrounding soft tissues, and relatively reduced risk of needle stick injury. This study evaluates the efficacy of IMF screws over arch bar IMF before defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…This was significantly more when compared with Nandini et al 9 (8.52 ± 2.7 minutes). Barodiya et al 10 and Qureshi et al 6 documented the time range similar to our study: 16.1 and 15.56 minutes respectively.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This was significantly more when compared with Nandini et al 9 (8.52 ± 2.7 minutes). Barodiya et al 10 and Qureshi et al 6 documented the time range similar to our study: 16.1 and 15.56 minutes respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Rai et al 8 in a comparative study also reported more plaque accumulation in patients treated using Erich arch bars as compared with MMF screws. Similar results were documented by Qureshi et al, 6 Nandini et al, 9 and Barodiya et al 10 They found a significant difference between the plaque index values of both the groups and based on this, they concluded that maintenance of oral hygiene is better in patients treated using MMF screws.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Some authors suggest that the use of IMF screws is less time consuming, provides better oral hygiene and reduces the risk of needle stick injury. 12,13 Conversely, use of IMF screws is associated with teeth root damage and screw loosening leading to instability of MMF. Despite these disadvantages, IMF screws are suggested as an alternative to arch bar for achieving IMF in the management of maxillofacial trauma.…”
Section: Introductionmentioning
confidence: 99%